2008
DOI: 10.1542/peds.2007-2243b
|View full text |Cite
|
Sign up to set email alerts
|

Early Developmental Processes and the Continuity of Risk for Underage Drinking and Problem Drinking

Abstract: Developmental pathways to underage drinking emerge before the second decade of life. Many scientists, however, as well as the general public, continue to focus on proximal influences surrounding the initiation of drinking in adolescence, such as social, behavioral, and genetic variables related to availability and ease of acquisition of the drug, social reinforcement for its use, and individual differences in drug responses. In the past 20 years, a considerable body of evidence has accumulated on the early (of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
250
0
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(281 citation statements)
references
References 166 publications
(194 reference statements)
20
250
0
8
Order By: Relevance
“…Both prospective and retrospective studies have demonstrated a strong relationship between these two childhood disorders and later alcohol misuse when the two are allowed to co-exist naturally (Flory and Lynam, 2003;Schuckit et al, 2008;Tarter et al, 2003;Zucker et al, 2008). Our current study examined how childhood ADHD and childhood CD predicts later adult alcoholic drinking.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Both prospective and retrospective studies have demonstrated a strong relationship between these two childhood disorders and later alcohol misuse when the two are allowed to co-exist naturally (Flory and Lynam, 2003;Schuckit et al, 2008;Tarter et al, 2003;Zucker et al, 2008). Our current study examined how childhood ADHD and childhood CD predicts later adult alcoholic drinking.…”
Section: Discussionmentioning
confidence: 89%
“…Such observations have been reported by others, especially for boys . Investigators who have compared children of alcoholic and nonalcoholic parents typically fi nd more impulsivity and emotional deregulation among the offspring of alcoholics (Sher, 1991;Zucker et al, 2008). These differences between high-risk and low-risk offspring have been noted even at very early ages.…”
mentioning
confidence: 99%
“…Health and academic data were gathered in the demographic survey from both youth and one parent, including aspects of functioning associated with initiation of drinking in this age range (e.g., Anderson & Brown, 2011;Brown et al, 2008;Zucker et al, 2008). Most (85%) participants had Notes: NCANDA = National Consortium on Alcohol and NeuroDevelopment in Adolescence; OHSU = Oregon Health & Science University; SRI = SRI International; UPMC = University of Pittsburgh Medical Center; UCSD = University of California, San Diego.…”
Section: Current Health and Psychosocial Functioningmentioning
confidence: 99%
“…Gaining a better understanding of alcohol use effects during this crucial developmental stage has been positioned in national scientific consciousness and federal funding initiatives over the past two decades (Brown et al, 2008;Windle et al, 2008). Cross-sectional studies have identified brain structural and functional abnormalities (Cservenka et al, 2014;De Bellis et al, 2005McQueeny et al, 2009;Nagel et al, 2005;Petit et al, 2014;Schweinsburg et al, 2010;Tapert et al, 2004), neurocognitive deficits (Brown et al, 2000;Silveri, 2014;Whelan et al, 2014;Xiao et al, 2013), and poorer psychosocial functioning (Anderson et al, 2010;Brown et al, 2008;Fergusson & Lynskey, 1996;Zucker et al, 2008) in heavydrinking adolescents relative to non-/low (NON) drinking counterparts. Deleterious effects of alcohol consumption have been associated with heavy drinking episodes (Chassin et al, 2002;McQueeny et al, 2009), defined as consuming four or more drinks on a single occasion for females and five or more drinks for males (National Institute on Alcohol Abuse and Alcoholism [NIAAA], 2004;Wechsler et al, 1995).…”
mentioning
confidence: 99%
“…Portions of this research were presented as a poster at the 32nd annual meeting of the Research Society on Alcoholism, June 20-24, 2009, San Diego, CA. ā€  Correspondence may be sent to John E. Donovan at the above address or via email at: donovanje@upmc.edu. R ISK FACTORS FOR ADOLESCENT DRINKING can be divided into two main categories: alcohol-specifi c risk factors and general risk factors (Zucker et al, 2008). To date, there have only been a few studies of the development of alcohol-specifi c risk factors from childhood into adolescence (Andrews and Peterson, 2006;Andrews et al, 2003;Donovan et al, 2009).…”
mentioning
confidence: 99%